TECHNIQUES TO MINIMIZE THE EFFECTS OF ACUTE HEAT STRESS OR CHRONIC IN BROILERS - Rodrigues,MM (2019)
ABSTRACT High environmental temperature is limiting factor in broiler production. In order to minimize the undesirable consequences of acute or chronic heat stress, the techniques of fixed dietary electrolyte balance and early heat conditioning were evaluated. The objective of this study was to evaluate the possible interactions and effects of dietary electrolyte balance and early heat conditioning on feed intake, body weight, feed conversion ratio, mortality, energy bioeconomic index, fecal moisture, abdominal fat, and breast meat color (L*a*b*) of broilers submitted to chronic or acute heat stress. In total, 1280 chicks, were equally divided in experiment I (chronic heat stress, 6h/day at 32ºC from 35 to 39 d of age) and II (acute heat stress, 36 ºC for 6h at 38 days of age). The data of both experiments were combined and analyzed according to a 2x2x2 factorial arrangement (early heat conditioning (ETC) or not; fixed dietary electrolyte balance (EB) or not; and exposure to acute or chronic heat stress). ETC consisted of exposing 5-d-old birds to 36.0 °C for 24 hours. No interaction among the evaluated factors was detected. Birds exposed to acute heat stress presented significantly higher compared with chronic heat stress. Fixed dietary EB resulted in significantly higher fecal moisture. Lower abdominal fat percentage was obtained in birds exposed to chronic relative to acute heat stress. Higher breast meat L* and b* values were observed in birds exposed to acute heat stress than those submitted to chronic heat stress, indicating worse meat quality.